Prognostic Significance of NLR About NETosis and Lymphocytes Perturbations in Localized Renal Cell Carcinoma With Tumor Thrombus - Shang, Bingqing; Guo, Liping; Shen, Rongfang; Cao, Chuanzhen; Xie, Ruiyang; Jiang, Weixing; Wen, Li; Bi, Xingang; Shi, Hongzhe; Zheng, Shan; Li, Changling; Ma, Jianhui; et al. (Frontiers in Oncology, 2021)
Background: Non-metastatic renal cell carcinoma (RCC) with tumor thrombus showed a greater tendency for developing metastases after surgery. Early identification of patients with high risk of poor prognosis is especially important to explore adjuvant treatment of improving outcomes. Neutrophil to lymphocyte ratio (NLR) was a systemic inflammation marker and outcome predictor in RCC, inflecting the chaos in systemic immune status in cancer as myeloid cell expansion and lymphatic cell suppression. Neutrophil extracellular traps (NET) formation (NETosis) is the process of neutrophils generating extracellular DNA net-like structure. NETosis in tumor was demonstrated to conduce to the subsequent metastases of tumor. However, the role of NLR for systemic immune status and tumor local immune infiltration, especially for Neutrophils associated NETs, in non-metastatic RCC with thrombus remains unclear. Patients and Methods: In our clinical cohort, we enrolled the clinical, pathologic, and pre-operative laboratory parameters of 214 RCC patients with tumor thrombus who were treated surgically. The clinical endpoint was defined as cancer specific survival (CSS). In our basic research cohort, RNA-seq, TCR-seq and scRNA-seq data were analyzed. Patients who reached the endpoint as recurrence-free survival (RFS) were defined as the “High-risk” group. Otherwise, they were separated into the “Low-risk” group. Results: In the clinical cohort, NLR≥4 was an independent risk factor for 203 localized RCC with tumor thrombus. In the basic research cohort, tumor thrombi were separated into NETosis-thrombi belonging to the “High risk” group and non-NETosis-thrombi to the “Low risk” group. NETs induced by tumor-derived G-CSF in tumor thrombus has a mechanistic role in unfavorable prognosis. Besides, NETs-score from single sample GSEA (ssGSEA) algorithm was an independent prognostic factor validated in the TCGA data. Apart from the neutrophils associated NETosis, systemic immune perturbations of lymphocytes occurred in the “High risk” group, represented with decreased TCR diversity and increasingly high proportion of CD4 positive effector memory T (Tem) cells which indirectly represented the state of lymphopenia. Conclusions: Our findings firstly demonstrated that neutrophils associated NETosis and systemic lymphocytes perturbations were considered as tumor progression in patients of localized RCC with tumor thrombus, which reflected NLR≥4 as an independent risk factor for patients.